Direct Replication and Additional Sensitivity and Robustness Analyses for Frederiksen (2022): A Replication Report from the Nottingham Replication Games - Thomas Brailey; Matthew Hepplewhite; Scott Moser (Institute for Replication (I4R), 2023)
We replicate the analysis conducted by Frederiksen, 2022a. We focus on assessing the computational and robustness replicability of their work. We find that their main exhibits and supplementary analysis are replicable, both when running their original Stata replication package, and when we attempt to replicate their findings from scratch in R. We also conduct additional robustness checks by estimating additional specifications and by subsetting the dataset by the time taken by the respondent to complete the survey. We again find that their work is robust to our battery of alternative specifications.
Keywords: 330